Emotional intelligence predicts academic achievement in Pakistani management students. Issue 2 (July 2019) - Ahmed, Zahid; Asim, Muhammad; Pellitteri, John
Abstract: Emotional Intelligence (EI) has been identified as an emerging area that influences academic achievement. Previous studies found conflicting results in this relationship as well as in gender differences both within Pakistan and in other countries. The purpose of this study is to examine the relationships between EI, academic achievement and gender differences for Pakistani management students. The correlational and group comparison methods were based on a sample of 189 participants (106 males and 83 females). The results of this study established EI as a predictor of academic achievement. The Self-Control, Sociability and Well-being components of the Trait Emotional Intelligence Questionnaire (TEIQue) were positively correlated with GPA while the Emotionality component was negatively correlated. The negative correlations between Self-control and both Emotionality and Sociability differed from the normative sample of the TEIQue suggesting notable cultural differences. Patterns of gender differences found males scoring higher on Self-control and Well-being while women scored higher on Emotionality. Issues such as language-based self-report formats and cultural differences in emotion socialization were considered. Recommendations suggest that universities include EI development as part of the academic process and that male and female students would require different types of EI support.